1031 Assessing the implications of pervasive solutions to assist risk prevention: the case of home health monitoring. (1st September 2016) - Wickramasinghe, Nilmini; Haddad, Peter; Schaffer, Jonathon
Abstract : Background: The advancing age of the baby boomer, coupled with increased life spans, has led to a significant increase in the number of senior citizens in many countries. Providing care for this population in the acute care setting is only one aspect of the total care package that needs to be addressed. For those having been in the acute care setting for either medical treatment or following procedural based therapies, the discharge to home often provides an opportunity to continue the post acute care monitoring to ensure that complications or readmissions do not occur. Monitoring care and providing guidance and medical management at home will offer patients, families, facilities and providers with the opportunity to ensure recovery and return to a healthy steady state. To explore this issue further, the following examines the possibilities for monitoring post-operative clinical functions in the context of total knee and/or total hip athroplasty, by proposing a conceptual model that can then guide a randomised clinical trial to test the presented hypotheses and model. Methods: In this research a qualitative approach using an exemplar data site as a single exploratory case study is adopted to explore main components, barriers, issues and requirement to design and develop a home monitoring technology in senior citizens to detect post-operative complications and risk factors in the case of Hip & Knee replacements. Results: Initial analysis has identified the following risk factors that need to be monitored at home: depression, hypertension, post-operative hyperglycemia, infection, instability, loss-of-Motion, BMI (body Mass Index). Further, analysis of the study population between 2004 to 2012 depicted that during this time 4645 patients (60+) had hip replacements while 4790 had knee replacements operations. Conclusions: The implications of this study are far reaching both from the stand point of quality of life and care as well as from an economic stand point.